2000
DOI: 10.15760/etd.706
|View full text |Cite
|
Sign up to set email alerts
|

Somatization and Engagement in Mental Health Treatment

Abstract: Somatization, the presentation of physical symptoms without an identifiable cause, is among the most common problems in primary medical care. Treatment approaches are typically offered within the medical consultation interview once the medical provider distinguishes between physical and emotional etiology. This dualistic strategy is especially troublesome for patients whose physical complaints cannot be validated and who are recommended for only mental health therapy. The aim of this study was to examine how m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…Research shows that doctors can strongly influence patients’ motivation for treatments of all kinds (Di Blasi, Harkness, Ernst, Georgiou, & Kleijnen, ). Chianello () designed an enhanced GP consultation and referral script to address the key sensitivities of patients with MUS highlighted in the literature. In a simulation study, this script increased motivation to attend therapy with a medium effect size.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that doctors can strongly influence patients’ motivation for treatments of all kinds (Di Blasi, Harkness, Ernst, Georgiou, & Kleijnen, ). Chianello () designed an enhanced GP consultation and referral script to address the key sensitivities of patients with MUS highlighted in the literature. In a simulation study, this script increased motivation to attend therapy with a medium effect size.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a city mayor was sued in 2018 for blocking political activists from his personal Twitter account, on the alleged grounds that he was violating their rights under the Canadian Charter of Rights and Freedoms. 73 74 It was reported that "By blocking some residents, the lawsuit alleges, the mayor is denying them the "ability to engage in debate concerning municipal issues using Twitter," which the applicants argue is now a vital method of communication for public officials." 74 The mayor later conceded that the account was used to conduct dayto-day duties and unblocked the individuals 75 ; thus, the case was not tested in court.…”
Section: Discussionmentioning
confidence: 99%
“…73 74 It was reported that "By blocking some residents, the lawsuit alleges, the mayor is denying them the "ability to engage in debate concerning municipal issues using Twitter," which the applicants argue is now a vital method of communication for public officials." 74 The mayor later conceded that the account was used to conduct dayto-day duties and unblocked the individuals 75 ; thus, the case was not tested in court.…”
Section: Discussionmentioning
confidence: 99%
“…The options had minor distinguishing elements, but they were really two of the same thing: more federal office buildings, a commercial tower near the Tunney's transit station and condos along Parkdale Avenue. 31 Following the community consultation, Kitchissippi councillor Katherine Hobbs said, "the federal government needs to dramatically rethink its plans." 32…”
Section: Canned Solution Reevaluating Hok's Master Planmentioning
confidence: 99%